Promoting In-House Library Use in Knowledge Era - Nikam, Khaiser (Journal of Information and Knowledge, 2001)
This paper intends to present the significance of promoting library use in the knowledge era. It states the key concepts of promotion with special reference to market program. Promotion as a marketing tool with various techniques is discussed in detail. It also gives an idea about the problems of promoting library use.